2014
DOI: 10.1021/ja503283r
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Self-Assembly of Giant Bottlebrush Block Copolymer Surfactants as Shape-Tunable Building Blocks

Abstract: Programmed self-assembly of well-defined molecular building blocks enables the fabrication of precisely structured nanomaterials. In this work, we explore a new class of giant polymeric surfactants (Mn = (0.7-4.4) × 10(6) g/mol) with bottlebrush architecture and show that their persistent molecular shape leads to the formation of uniform aggregates in a predictable manner. Amphiphilic bottlebrush block copolymers containing polylactide (PLA) and poly(ethylene oxide) (PEO) side chains were synthesized by a graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
248
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(267 citation statements)
references
References 64 publications
10
248
0
4
Order By: Relevance
“…In some cases vesicles with total lengths of several hundred nanometres were observed. This work demonstrates the self-assembly of bottlebrushes to form large (> 100 nm) nanocarriers in water 10 . In vivo studies demonstrated preferential localization of bottlebrush micelles in tumor sites 42 (Fig.…”
Section: Bottlebrush Assemblies In Solution For Delivery and Interfacmentioning
confidence: 79%
“…In some cases vesicles with total lengths of several hundred nanometres were observed. This work demonstrates the self-assembly of bottlebrushes to form large (> 100 nm) nanocarriers in water 10 . In vivo studies demonstrated preferential localization of bottlebrush micelles in tumor sites 42 (Fig.…”
Section: Bottlebrush Assemblies In Solution For Delivery and Interfacmentioning
confidence: 79%
“…Upon further addition of SA, a slight increase in cmc was noticed while γ cmc first decreases, reaches a minimum at ρ = 0.5, and then increases slightly ( Figure 1B and Table 1). 1 H NMR measurement of three typical samples ( Figure S1) indicates that the SA/C 14 DMAO complex is 1:2 stoichiometric, which is consistent with the results obtained by Sakai et al 32 and Douliez et al 33 A closer inspection reveals that at ρ = 0.4 and 0.7, two break points can be detected in the curves ( Figure S2), indicating that conformational changes and multistep selfassembly of SA/C 14 DMAO mixtures occur at the air/water interface. 39 The variation of cmc and γ cmc with ρ can be understood by taking into account two factors.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In fact, the properties of PLA/PEG analogues copolymer and resulting micelles are affected by the hydrophobic/ hydrophilic balance, the ratio of comonomers, the graft density, the graft length etc. (Bakkour et al, 2013;Fenyves et al, 2014;Luzón et al, 2010;Saeed et al, 2009 Fig. 2 presents the SEC curves of the copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…These PEG analogues exhibited a LCST between 26 and 90 C which can be precisely adjusted by varying the co-monomers ratio, which could be attractive for targeted drug delivery because of their thermo-responsive properties and outstanding biocompatibility similar to linear PEG. Later on, the synthesis and micellization of PLA/PEG analogues copolymers have been studied (Bakkour et al, 2013;Fenyves et al, 2014;Luzón et al, 2010;Saeed et al, 2009). Nevertheless, the LCST of these copolymers was above 75 C, which greatly diminishes their potential as drug carrier.…”
Section: Introductionmentioning
confidence: 99%